What the Book of Mormon Is - Sperry, Sidney B. (Journal of Book of Mormon studies, 1995)
The records of the Nephite, Jaredite, and Mulekite peoples comprise the Book of Mormon, of which Mormon is the principal editor. Four divisions are evident, namely, the small plates of Nephi, Mormon's explanatory notes, the literary labors of Mormon, and the literary labors of Moroni. The first division, the small plates of Nephi, is analyzed in this chapter.